Safeguarding Public Health From Farms To Markets To Househods - Abaidoo, Robert C. (2009)
Urban and peri-urban agriculture (UPA) has becoming an important livelihood in developing countries, as fast growing population demand more food and water. UPA contribute to urban food security -in several African cities between 50 and 90 percent of the vegetables consumed are produced in city backyard or just outside the city limits in small farms. But growing demand for industrial and domestic water need is leaving famers with little alternative but to use some of the large volume of wastewater release for urban areas for irrigation. In Ghana and Burkina Faso, the pressure from urban centers dependent on water resources from the Volta basin has made wastewater use in UPA a common practice. In many part of the basin wastewater is the only available surface water for irrigation in the dry season and a reliable nutrient-rich source that secures the livelihoods of famers engaged in UPA